El Excentrico, 1968-08-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
August 20, 1968 [20 de Agosto de 1968]. No Volume or issue number. Cover has a closeup photo of a women advertising for the Furniture Discount House.